Risk and protective factors for anxiety impacting academic performance in post-secondary students - Lisnyj, Konrad T.; Russell, Regan; Papadopoulos, Andrew (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2020)
This survey study measured the association between risk and protective factors of anxiety and its implications on the academic performance of 1,053 students at a four-year, public post-secondary institution in southwestern Ontario. Logistic regression analyses revealed 13 significant variables at the univariable level, while the multivariable model yielded seven significant factors. Students who felt hopeless significantly increased their odds of reporting anxiety adversely affecting their academic performance, while being able to manage daily responsibilities was the only protective factor against anxiety impacting students’ educational attainment. By planning, designing, and implementing proactive programs focusing on thesepredictor variables, such interventions can equip students against the debilitative influence of anxiety on their academic success.